PENYELESAIAN SENGKETA PERDATA MELALUI GUGATAN SEDERHANA (SMALL CLAIM COURT) DI PENGADILAN NEGERI KELAS 1 A PADANG - Mardius , (Fakultas Hukum Universitas Tamansiswa Padang, 2018)
Dispute resolution by giving authority to the court to settle cases based on the value of the object of the dispute, so that dispute resolution can be achieved quickly, simply and lightly according to PERMA Number 2 of 2015, in filing a claim, the maximum value of the case object is Rp.200,000,000 , 00 (two hundred million rupiah) with a simple verification process and led by a single judge with a Small Claim Court, so that dispute resolution can be achieved quickly, simply and at a low cost, but still provide legal force in the form of a judge's decision that has the power forced to be carried out (binding force). In the process of civil dispute resolution through the settlement of a simple lawsuit in the Class 1 A Padang District Court is the registration of a Simple Claim, a simple lawsuit examination, the determination of a judge and the appointment of a substitute clerk, a preliminary examination, the determination of the day of the hearing, the first hearing and peace, proof and verdict.